(untitled) (Tanzania Medical Journal, 2015)
Background: Sickle cell disease and glucose-6-phosphate dehydrogenase (G-6-PD) deficiency are relatively common genetic disorders in population exposed to malaria in sub-Saharan Africa. The prevalence of these two genetic disorders differs between different malaria transmission areas.Objectives: This cross sectional study was conducted to determine the prevalence and co-existence of sickle cell, malaria and G6PD deficiency in school children and determine their association with anaemia.Methods: Venous blood samples from 385 school children aged 9 to 18 years and then fluorescent spot test, cyanmethaemoglobin, sickling test and haemoglobin electrophoresis methods were performed to determine G6PD deficiency, haemoglobin level and sickle cell traits. Two thick and one thin smear were prepared from the obtained blood samples for diagnosis of malaria parasites parasitaemia.Results: Of 385 children 63(16.4 %) were found to have malaria parasites; sickle cell traits/ disease and G-6-PD deficiency was observed in 40(10.4 %) and 20 (5.2 %) respectively. The prevalence of G6PD deficiency + malaria, sickle cell traits + malaria and sickle cell + G6PD deficiency were 6.3%, 20% and 10% respectively. Low hemoglobin (<100mg/dl) was observed in 157 (40.8 %) of children. Asymptomatic malaria and G6PD deficiency were found significantly to contribute to low hemoglobin among school children (P<0.001). Schools with higher prevalence of asymptomatic malaria had also higher prevalence of both G6PD deficiency and sickle celltraits (P<0.05). Malaria, anaemia and genetic disorders were significantly found more in peri-urban school than urban schools (p=0.0001).Conclusion and recommendation: Asymptomatic malaria infection is prevalent in individuals with G6PD deficiency and sickle cells traits in our setting, and this confirms the protection of genetic disorders against severe malaria. School children from peri-urban schools were more affected by malaria, anaemia and genetic disorders, more studies are recommended in these areas.